Properties of Porous InGaNbased Hydrogen Gas Sensor - Radzali, R.; Hassan, Z.; Zainal, N.; Yam, F.K. (2015)
The research of porous Ill-Nitrides has drawn much attention in the past years. This is due to porous Ill-Nitrides excellent properties such as high surface area to volume ratio, the shift of band gap and efficient luminescence which makes the porous Ill-Nitrides become attractive for the application in optoelectronics and sensing devices. In this work, the development of gas sensors based on PtSchottky contact on porous lnGaN for hydrogen gas sensing ispresented. Porous lnGaN samples were successfully fabricated by UV-assisted electrochemical etching in a diluted solution of KOH. ,........._ From the field emission scanning electron microscopy (FESEM) image, the porous lnGaN sample exhibited rough surface morphology with a high density of pores. Subsequently, for the fabrication of gas sensors, Schottky contacts of using platinum (Pt) that acted as catalytic layer were deposited on as-grown and porous lnGaN samples. The effects of porous structure on the performance of the hydrogen gas sensor was investigated. The PUporous lnGaN gas sensor showed higher sensitivity than the as-grown lnGaN gas sensor upon introduction to 0.1% H2 in N2 at room temperature. The high sensitivity of porous gas sensor was due to thehigh surface to volume ratio of the porous structure. The high sensitivity of hydrogen gas sensor is required to make sure the safety of people, property and environment whenever hydrogen gas is consumed.